2018
DOI: 10.1111/clr.13258
|View full text |Cite
|
Sign up to set email alerts
|

Immediate placement and provisionalization of implants in the aesthetic zone with or without a connective tissue graft: A 1‐year randomized controlled trial and volumetric study

Abstract: ObjectiveTo volumetrically compare peri‐implant mid‐facial soft tissue changes in immediately placed and provisionalized implants in the aesthetic zone, with or without a connective tissue graft.Material and methodsSixty patients were included. All implants were placed immediately after extraction. After randomization, in one group, a connective tissue graft (test group, n = 30) was inserted at the buccal aspect of the implant. The other group (control group, n = 30) received no connective tissue graft. Clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
230
1
24

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(270 citation statements)
references
References 23 publications
15
230
1
24
Order By: Relevance
“…independently and in duplicate examined the titles and abstracts. Eleven studies were suitable for full‐text evaluation, of which, seven studies were excluded . The remaining four trials were counted in the present review (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…independently and in duplicate examined the titles and abstracts. Eleven studies were suitable for full‐text evaluation, of which, seven studies were excluded . The remaining four trials were counted in the present review (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, favourable anatomical factors such as a thick gingival biotype (Bittner et al., 2019; Chen, Darby, Reynolds, & Clement, 2009; Kan, Rungcharassaeng, Lozada, & Zimmerman, 2011) and a thick (>1 mm), intact buccal bone wall (Chappuis et al., 2013; Kan, Rungcharassaeng, Sclar, & Lozada, 2007) seem of major importance to prevent hard and soft tissue collapse. However, even with strict case selection and protective interventions such as connective tissue grafting (van Nimwegen et al., 2018; Zuiderveld, Meijer, den Hartog, Vissink, & Raghoebar, 2018) and immediate restoration (De Rouck, Collys, Wyn, & Cosyn, 2009) aesthetic complications may develop over time despite satisfactory initial results (Cosyn et al., 2016; Kan et al., 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly, data have suggested that gingival recession happened on the anterior maxilla within 1 year of implant placement (Atieh, Payne, Duncan, & Cullinan, 2009;Cooper et al, 2010;van Nimwegen et al, 2018). The main reason for the unfavorable outcome is the resorption of facial alveolar bone wall (Bonnet, Karouni, & Antoun, 2018;Lanza et al, 2017).…”
Section: Introductionmentioning
confidence: 99%